Research on end hopping and spreading for active cyber defense - Leyi SHI; Hongbin GUO; Xiao WEN; Jianlan LI; Yuwen CUI; Mengfei MA; Hui SUN (Tongxin xuebao)
Inspired by the spread spectrum technology for communications,the concept of end spreading was proposed to represent a piece of information of the data transmission with a sequence of multiple end information,of which each piece of end information was irrelevant to the information it conveys.Thus the covert data transmission can be performed.Further,an active cyber defense model of end information hopping and spreading was presented,in which the hopping strategy was separated from the synchronization strategy.The synchronization was accomplished by means of end information spreading for synchronous authentication of both parties,which can solve the high-speed hopping synchronization problem with high concealment requirements.The mode of generation,transmission and authentication of the spreading sequence,and the data migration strategy in the end hopping and spreading model were described in detail,and the security performance and synchronization performance were analyzed and verified experimentally.Theoretical analysis and experimental results show that the cyber defense model of end information hopping and spreading has improved the availability and confidentiality of network services under high-speed hopping and has good anti-attack performance,which is of great significance for the proactive defense application of high intensity confrontation.